KINERJA METODE RESAMPLING JAKKNIFE UNTUK PEMETAAN LAHAN - Reinhart, Reinhart (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Classifications of impervious land and non impervious land using resampling Jackknife method are meant to test the method in land mapping. Area that being used in this research are Jakarta, Bogor, Depok, Tangerang, and Bekasi. Image data that being used are from satellite images Landsat-8 band 1, 2, 3, 4, 5, 6 and 7. The image data that used are from 2014, 2015, and 2016. The results of classifications will show how many land belong to impervious land and how many belong to non impervious land. The resampling Jackknife method that being used are resampling Jackknife mean, Jackknife median, and Jackknife first quartile. To test the detection the result will be compared to the real data. In Jakarta the Impervious land is bigger than non impervious land. While in Bogor, Depok, Tangerang, and Bekasi the non impervious land is bigger than the impervious land. The accuracy of resampling Jackknife method in land mapping is considerably good, it can detect which area is impervious, forest, river, or empty land .